Like father, like son - Patterson, James, 1947- (Patterson, James, 1947- Ali Cross series., 2022)
Washington D.C. middle schooler Ali Cross is determined to find out who shot his crush Zoe Knight. When he and his friends begin investigating what happened, they learn about the effects of gun violence on the black community and get involved in working for change.